Dynamic volume perfusion computed tomography parameters versus RECIST for the prediction of outcome in lung cancer patients treated with conventional chemotherapy - Janssen, Sonja; Schmid-Bindert, Gerald; Manegold, Christian; Pilz, Lothar R.; Schönberg, Stefan; Henzler, Thomas (Journal of thoracic oncology, 2015)
To compare dynamic volume perfusion computed tomography (dVPCT) parameters with Response Evaluation Criteria in Solid Tumors (RECIST 1.1) for prediction of therapy response and overall survival (OS) in non-small-cell lung cancer (NSCLC) and small-cell lung cancer (SCLC) patients treated with conventional chemotherapy. A total of 173 lung cancer patients (131 men; 61 ± 10 years) undergoing dVPCT before (T1) and after chemotherapy (T2) and follow-up were prospectively included. dVPCT-derived blood flow, blood volume, mean transit time, and permeability (PERM) were assessed, compared between NSCLC and SCLC and patients’ response to therapy was determined according to RECIST 1.1. One hundred of one hundred and seventy-three patients underwent dVPCT at T1 and T2 within a median of 44 (range, 31-108) days. dVPCT values were differing in NSCLC and SCLC, but were not significantly differing between patients with partial response, stable, or progressive disease. Eighty-five patients (NSCLC = 72 and SCLC = 13) with a follow-up for greater than or equal to 6 months were analyzed for OS. Fifty-six of eighty-five patients died during follow-up. Receiver operating characteristic analysis determined T1/T2 with highest predictive values regarding OS for blood flow, blood volume, mean transit time, and permeability (area under the curve: 0.53, 0.61, 0.54, and 0.53, respectively, all p > 0.05). Kaplan-Meier statistics revealed OS of patient groups assigned according to dVPCT T1/T2 cutoff values was not differing for neither dVPCT parameter, whereas RECIST groups significantly differed in OS (p = 0.02). Cox proportional hazards regression determined progressive disease status to independently predict OS (p = 0.004), while none of the dVPCT parameters did so. dVPCT values, differ between NSCLC and SCLC, are not related to RECIST 1.1 classification and do not improve OS prediction in lung cancer patients treated with conventional chemotherapy.